2019
DOI: 10.14735/amko2019306
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Surgical Treatment of GIST of Esophago-Gastric Junction in a Patient with Giant Hiatal Hernia

Abstract: Gastrointestinal stromal tumors (GISTs), being the most common mesenchymal tumors of the gastrointestinal tract, arise most commonly in stomach (60-70%) and small intestine (20-25%) while other sites of origin are rare. In most cases, they are dia gnosed accidentally due to their indolent clinical course; however, 10-30% have malignant potential. Gastric and esophageal GISTs carry a better prognosis than small bowel GISTs of similar size and mitotic rate. Complete surgical resection is the only potentially cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Another noteworthy aspect of this case is that we conducted an emergent operation. Esophageal GISTs do not typically present as surgical emergencies, and hence, there are very few published examples of management in such situations [4][5][6][7][8]. One such example by Romic et al reported an emergent "en bloc" resection of a 11 × 10 cm esophagogastric junction GIST due to uncontrollable GI bleeding after initiation of palliative imatinib therapy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another noteworthy aspect of this case is that we conducted an emergent operation. Esophageal GISTs do not typically present as surgical emergencies, and hence, there are very few published examples of management in such situations [4][5][6][7][8]. One such example by Romic et al reported an emergent "en bloc" resection of a 11 × 10 cm esophagogastric junction GIST due to uncontrollable GI bleeding after initiation of palliative imatinib therapy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms of esophageal GISTs are dysphagia and gastrointestinal bleeding [3] and it is rare for esophageal GISTs to cause significant or life-threatening hemorrhage. Very few cases have been reported [4][5][6][7][8], and only one case describes an esophageal GIST hemorrhaging into the thoracic cavity [9], making this an extraordinarily rare phenomenon. Surgical management, either by esophagectomy or enucleation, is indicated in esophageal GIST and obtaining a margin-negative resection is the goal [3].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment modality for non-metastatic GISTs is surgical resection with negative margins without lymph node resection [ 7 ]. To minimize the risk of local recurrence and metastatic expansion of GISTs, it is critical to achieving complete excision of localized disease with tumor spillage being prevented [ 13 ]. The definitive diagnosis of GIST is based on histology and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The operation of choice among many surgeons is en bloc resection with a negative margin because ileocolonic and colon-colonic lesions have a greater incidence of malignancy [ 13 ]. The metastasis and risk of local recurrence of GISTs are decreased with complete resection of the localized lesion [ 14 ]. Histopathological examination and immunohistochemistry studies help in the accurate diagnosis of GISTs.…”
Section: Discussionmentioning
confidence: 99%